The Creation of the SnaPhys (Snake Physics) Game as a Learning Medium for Physics on Renewable Energy Topics - Nur’aini, Velisa; Haryani, Fairusy (Journal of Advances in Physics Education, 2025)
The quality of the learning process affects student learning outcomes. The learning process is still limited to the teacher’s explanation and does not utilise learning media based on the characteristics of students. This impacts students' low motivation to learn, especially in Physics. This research aims to produce educational snake and ladders game products integrated with QR codes as an alternative physics learning media. The development model used is 4D. However, this research is limited to the 3D stage: define, design, and develop. The data collection technique used a questionnaire with a research subject of 1 expert. Experts will perform product validation in three aspects: technical, educational, and aesthetic. The results of data analysis showed that the technical aspect score was 17 with a percentage of 94.4%, the academic aspect score was 11 with a rate of 91.6%, and the aesthetic aspect score was 13 with a percentage of 86.6%. Thus, an average score of 41 with an average percentage of 91.1% was obtained so that the Snakes and Ladders game was included in the outstanding category and declared feasible to increase students' physics learning motivation.